2014
DOI: 10.1016/j.rmed.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sounds in healthy people: A systematic review

Abstract: Respiratory sounds show different acoustic properties depending on subjects' characteristics, subjects' position, respiratory flow and place of recording. Further research with robust study designs, different populations and following the guidelines for computerised respiratory sound analysis are urgently needed to build evidence-base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 36 publications
(108 reference statements)
1
29
0
5
Order By: Relevance
“…Such findings are related with the low number of crackles presented (TP) in these two respiratory sound files (1 9 crackles in the sound file), causing the few FP and FN to have a negative impact in the F-index. Nevertheless, this error might not have relevance for clinical practice as it has been reported that healthy people present approximately 4 crackles per breathing cycle 27 . Hence errors of this magnitude might not be clinically significant for diagnosis and monitoring of respiratory diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Such findings are related with the low number of crackles presented (TP) in these two respiratory sound files (1 9 crackles in the sound file), causing the few FP and FN to have a negative impact in the F-index. Nevertheless, this error might not have relevance for clinical practice as it has been reported that healthy people present approximately 4 crackles per breathing cycle 27 . Hence errors of this magnitude might not be clinically significant for diagnosis and monitoring of respiratory diseases.…”
Section: Discussionmentioning
confidence: 97%
“…30 Interestingly, the authors of a recent systematic review also found wheezing in 1%-5% and crackles in 7%-37% of healthy, asymptomatic adults from studies in the USA, but noted a gap in paediatric data, as there were no published studies that included healthy children. 31 Second, our expert listeners were blinded to the case-control status and also the visual cues that exist during a live patient encounter, and this may have increased false positive examinations; by looking at and listening to the patient at the same time, visual cues can help a clinician distinguish between wheezes, upper airway sounds such as cries, normal vocalisations, or transmitted nasal congestion (ie, the clinician can see the child crying, vocalising or rhinorrhea), or crackles and movement artefact (ie, the clinician can see the child moving), all of which can overlap in their amplitude and frequency profiles. 32 Notably, the majority of control lung sounds were recorded from Thailand (58.8% (167/284)), as this was the only site to enrol all controls into the digital auscultation substudy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review on respiratory sounds in healthy people, these methodological diff erences were also observed (36). Guidelines for research and clinical practice in the fi eld of respiratory sounds have been published in 2000 by the CORSA project group (34).…”
Section: Discussionmentioning
confidence: 99%